Pediatric Acute Care Simulator Case: Apnea - Mark Adler; Jennifer Trainor; Viva Siddall; William McGaghie (Association of American Medical Colleges, 2008)
Abstract This module is one of a series of four pediatric simulation cases developed as part of a performance evaluation research project. The case consists of a case scenario in which a 6-year-old is brought to the emergency department by an ambulance having been found unresponsive at his grandmother's house. This material would be useful for formative evaluation of pediatric residents or as part of a larger set of cases for medium-stakes summative evaluation (e.g., end-of-year performance assessment in a residency program). The publication reviews the validation data. The instruments proved both reliable and valid for our subject audience of pediatric residents. Checklist rating instruments are a commonly used approach for simulation-based assessment, in part because they can produce highly reliable ratings if the raters are well trained and the instrument is fine-tuned. However, checklists are time-insensitive and may not match a more general/global assessment of a subject's performance. For example, a very slow, methodical subject would achieve an identical checklist score to a highly efficient performance using these tools.